Pengaruh Bekas Tekukan pada Besi Beton Terhadap Lenturan Balok - Karjanto, Adjib (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
In the world of construction, especially reinforced concrete work that uses concrete steel reinforcement, there are found bends of reinforced concrete iron which is straightened to be used as reinforcement for the concrete construction. This can be justified provided that it complies with the provisions of the applicable regulations in SKSNI. From the results of this study it was found that the iron beam experienced a bend there was an influence on the load carrying capacity it received. Beams with bends in the middle of the span experience greater bending than beams without bending bends. Furthermore, the beam with concrete iron that experienced one-quarter bending of the span stretched the second place in receiving the load compared to the beam that experienced iron bending in the middle. Next the concrete beam with bending in a quarter span on both sides also experienced a decrease in the strength of its carrying capacity against the load it received. From the whole study, the normal beam load (BN) of 28.00 kN was obtained with a flexing of 5.28 mm. Whereas for concrete beams with several types of iron with bending the average deflection is 9.65 mm with the same load of about 35.33 kN.